Self Efficacy and Person Job Fit as Determinants of Employee Performance: A Study on CV. Surya Gemilang Motor Surabaya - Achmad Zaki Fadhil; Waras Waras; Mochamad Syaiful Arif (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study aims to examine and analyze the effect of Self Efficacy and Person Job Fit on employee performance. The population of this research is employees of CV. Surya Gemilang Motor Surabaya. The sampling technique used Total Sampling, namely the technique of all members of the population used as a sample of 30 employees with marketing status at CV. Surya Gemilang Motor Surabaya. Data analysis techniques were performed using statistical tools with SPSS version 25. Based on the results of the t hypothesis test it is known that partially Self Efficacy and Person Job Fit have a significant effect on employee performance. Meanwhile, based on the results of the F test hypothesis test, it is known that simultaneously Self Efficacy and Person Job Fit have a significant effect on employee performance. Thus for CV. Surya Gemilang Motor Surabaya is advised to pay attention to the Self-Efficacy and Person Job Fit conditions of employees so that employee performance continues to increase.